Assessment of the hygiene and sanitation practices of students of class VI to IX in urban government inter college at Allahabad district, India - Anand, Deepak; Prakash, Shiv (International Journal Of Community Medicine And Public Health, 2018)
Background: Hygiene and sanitation practices directly affect health status, and students can be easily educated for correct practices, which can be a cheap and effective measure for disease prevention, also it will reduce absenteeism due to illness in schools. This research paper was designed to assess the factors influencing hygiene and sanitation practices among school children. Methods: It is a cross-sectional descriptive study, sample size was 400. Data was collected between August 2017 and December 2017 by using structured questionnaire on general hygiene and sanitation practices. Results: It was found that only 61.5% of students wash their hand before meals, merely 16.75% of them were practicing proper dental hygiene, 41.25% of them clean genitals properly, whereas 52.25% students daily consumes food from vendors. Significant difference in sanitation and hygiene practices was found regarding education of father, education of mother and socioeconomic status. Conclusions: Hygiene and sanitation practices among students are not satisfactory and there is scope for improvement.